2006
DOI: 10.1152/ajprenal.00190.2006
|View full text |Cite
|
Sign up to set email alerts
|

Collecting duct-specific knockout of the endothelin B receptor causes hypertension and sodium retention

Abstract: . Collecting duct-specific knockout of the endothelin B receptor causes hypertension and sodium retention. Am J Physiol Renal Physiol 291: F1274 -F1280, 2006. First published July 25, 2006 doi:10.1152/ajprenal.00190.2006.-Collecting duct (CD)-derived endothelin-1 (ET-1) inhibits renal Na reabsorption and its deficiency increases blood pressure (BP). The role of CD endothelin B (ETB) receptors in mediating these effects is unknown. CD-specific knockout of the ETB receptor was achieved using an aquaporin-2 prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
152
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(164 citation statements)
references
References 51 publications
10
152
1
1
Order By: Relevance
“…Similarly, Mattson et al (32) have demonstrated that chronic intravenous administration of the NO synthase inhibitor N G -nitro-L-arginine methyl ester (L-NAME) selectively decreases renal medullary blood flow, causes sodium and water retention, and leads to hypertension. Similar manifestations were noticed in rats with collecting duct-specific knockout to the ET B receptor (12). Taken together, these findings appeal to the notion that alterations in the endogenous NO system may contribute to the altered renal hemodynamics and kidney function seen in pneumoperitoneum.…”
supporting
confidence: 75%
“…Similarly, Mattson et al (32) have demonstrated that chronic intravenous administration of the NO synthase inhibitor N G -nitro-L-arginine methyl ester (L-NAME) selectively decreases renal medullary blood flow, causes sodium and water retention, and leads to hypertension. Similar manifestations were noticed in rats with collecting duct-specific knockout to the ET B receptor (12). Taken together, these findings appeal to the notion that alterations in the endogenous NO system may contribute to the altered renal hemodynamics and kidney function seen in pneumoperitoneum.…”
supporting
confidence: 75%
“…Urinary aldosterone concentration was determined by solid-phase RIA after extraction with ethylacetate (100%) according to the manufacturer's instructions (Siemens Medical), as described in ref. 46. In separate studies, we determined that acid hydrolysis (3.2 NHCl, 24 h, room temperature, in the dark) was not necessary; hydrolysis reduced measured values by Ͻ5% (97.7 Ϯ 3.8%).…”
Section: Methodsmentioning
confidence: 97%
“…The effect of Epo to increase renal NO production could be the consequence of the increase in ET-1 production, which is a well characterized stimulus for renal NO production. ET-1-induced renal NO production inhibits collecting duct sodium reabsorption in sufficient magnitude to lower BP in mice (60), conferring a potential counter-regulatory mechanism against Epo-induced hypertension and perhaps partially explaining the hypertensive response to l-NAME in Epo-treated rats and rabbits (55,56). Because the renal effect is likely to be less important for BP control in patients with more advanced GFR reduction, such patients may be more predisposed to hypertension.…”
Section: Epo's Effects On Nomentioning
confidence: 99%